Bank relationships and corporate governance : a survey of the literature from the perspective of SMEs - Pinto, António Pedro Soares (2015)
The aim of this work is to review and systematise the literature on how bank relationships, corporate governance and the interdependence between them can influence corporate performance. The banks and the enterprises establish relationships which enable them to overcome problems of asymmetrical information thereby alleviating difficulties felt in obtaining financial resources.In addition, the specificities that SMEs face, namely their ownership structure, as they are often owned and controlled by families, lead us to study the role played by corporate governance and the various control mechanisms in achieving corporate objectives. These features confer an important supervisory role on credit institutions which stem from the information they hold.